“Must the Police Refuse to Look?” Resolving the Emerging Conflict in Search and Seizure Over Civilian Disclosure of Digital Evidence - Diab, Robert (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2023)
Courts in Canada are dealing more frequently with an old problem in a new guise: civilians bringing police digital evidence that engages a suspect’s privacy interest (text messages, email). Do police carry out a seizure when they receive it or a search when they proceed to review it, even briefly? Should police ‘refuse to look’ before obtaining a warrant or other authorization? If so, why? What measure of protection would calling this a search or seizure under section 8 of the Charter afford Canadians? The Supreme Court of Canada has yet to decide these issues directly, and trial, appeal courts, and commentators have offered widely diverging responses to the questions they raise. In doing so, courts and commentators alike have lost sight of the Supreme Court’s principled approach to what constitutes a search or seizure and when it will be reasonable. Applying this approach in R v Marakah, McLachlin CJ in obiter held that receiving a text exchange from a third party would require police to obtain a warrant before reading it, but she provided no rationale. This article articulates the Court’s principled approach and shows why diverging approaches among recent courts and commentators are not compelling. More crucially, given how central digital communication has become to all of us, the article sets out a rationale for insisting on a warrant before police review texts or photos, and what is at stake in failing to provide this vital safeguard.